HIV/AIDS Survival Rate among Hill Tribe Population in Northern Thailand - Tawatchai Apidechkul (Siriraj Medical Journal, 2020)
Objective: To find out the current situation of HIV/AIDS, sexual behaviors, and survival times in the six main hill tribe populations in Thailand: Akha, Lahu, Karen, Hmong, Yao and Lisu, who live in northern Thailand where HIV/AIDS is of the highest prevalence in the country. Methods: A retrospective cohort study design was conducted with a systematic data extraction of medical records of hill tribe HIV/AIDS cases from 37 hospitals in 4 provinces, northern Thailand. Statistical data were analyzed by Survival analysis and Cox’s-Regression. Results: 608 cases were recorded of which 581 were suitable for analysis. 81.0% of subjects were alive at the time of study, 39.6% were aged 26-35 years at the time of diagnosis. 64.9% were female, 36.2% were Lahu, 29.8% were Karen, 57.7% were Buddhist, and 24.6% were Christian. 57.5% were infected by sexual intercourse, 6.2% were intravenous drug users (IDU). Those receiving antiretroviral drug (ARV) had a 50% survival time of 12.4 years whereas in the non-ARV group a 50% survival time was only 5.9 years (p ≤0.01). The 50% survival time of non-OI infection was 10.6 years whereas it was only 6.3 years for the OI group (p ≤0.01). Cox’s-regression model found that being female (HR 0.55; 95%CI 0.02-0.82), receiving ARV (HR 0.43; 95%CI 0.27-0.69), and having non-OI (HR 0.53; 95%CI 0.01-0.89) were factors favoring good survival. Conclusion: Improving the access to health care services for hill tribe HIV/AIDS are necessary as well as encouraging them to use condoms.